Metal organic framework material coated silicon sphere lithium ion battery negative electrode material and preparation method thereof
The core-shell structure of ZIF-8 coated nano-silicon spheres was prepared by one-step method, which solved the electrode powdering and low conductivity problems caused by volume expansion of silicon-based materials in lithium-ion batteries, and achieved efficient electrochemical performance and cycling stability sex.
Patent Information
- Application Number
- CN202211310661.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-10-25
AI Technical Summary
The volume expansion of the existing lithium-ion battery negative electrode material of silicon-based materials during charging and discharging leads to the electrode powdering and falling off, and the low conductivity affects the electron transmission and the diffusion of Li+, resulting in capacity attenuation, reduced Coulomb efficiency, poor rate performance and cycle stability .
The metal organic frame material ZIF-8 is prepared by a one-step method to coat nanosilicon spheres to form a core-shell structure, which improves the specific surface area and ionic conductivity of the material, buffers the volume expansion and shortens the transmission path of lithium ions.
It significantly improves the circulation performance and rate performance of the negative electrode materials of lithium-ion batteries, extends the cycle life of the battery, reduces production costs, and provides a way for large-scale industrial production.
Smart Images

Figure CN115663137B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium battery negative electrode materials, and particularly relates to a metal organic framework material coated silicon ball lithium ion battery negative electrode material and a preparation method thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Silicon-based materials have a high theoretical specific capacity (3600 mAh g at room temperature). -1 ), lower working potential (~0.4Vvs.Li / Li + ) and its abundant reserves and friendly price make it one of the candidates for the negative electrode material of the next generation of lithium-ion batteries. However, the inherent disadvantages of silicon-based materials limit their further application. For example, the drastic volume expansion (>300%) during the charge and discharge process causes a series of problems such as electrode powdering and shedding, and the continuous generation and destruction of the solid electrolyte interface (SEI) film, which leads to battery capacity decay and reduced coulomb efficiency. In addition, low conductivity is not conducive to the transmission of electrons and Li + The diffusion of lithium ions leads to poor rate performance and cycle stability of the battery. To address the above problems, there are two main aspects to solve them. (1) Structural design: Designing materials into porous silicon, silicon nanotubes, core-shell structures, etc. can effectively buffer the volume expansion during lithium insertion and extraction and shorten the transmission path of ions and electrons. (2) Material composite: The conductivity of silicon-based materials is increased by composite with materials with high electronic / ionic conductivity, thereby improving electrochemical performance.
[0004] Zeolitic imidazolate framework material (ZIF) is a special metal organic framework porous material with the advantages of high ionic conductivity, high specific surface area, good thermal / chemical stability, adjustable structure and pore size, etc., and is widely used as anode material for lithium ion batteries. So far, most of the electrode structure design and preparation methods for ZIF-8 and Si composite materials are to coat high-capacity silicon with ZIF-8 derivatives (nitrogen-doped carbon). The preparation process is complicated and the cost is high, which is not suitable for large-scale industrial production. However, there are few studies on the composite of pure ZIF and Si and its potential electrochemical performance. Seeking a simple and low-cost ZIF-8 and Si composite material has become a technical problem that needs to be solved in this field. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a high-performance lithium-ion battery negative electrode material having a core-shell structure, a metal organic framework material ZIF-8 coated nano-silicon sphere and a preparation method thereof. The obtained ZIF-8 coated silicon sphere is of nanometer or submicron magnitude, and the material exhibits a mixed morphology of rhombic dodecahedron-shaped ZIF-8 and spherical nano-silicon, and a layer of ZIF-8 is also coated on the surface of the silicon sphere. The material has a high specific surface area, and as a negative electrode material for lithium-ion batteries, it exhibits excellent cycle performance and rate performance. The ZIF-8 layer on the surface of the silicon sphere can provide abundant Li for the internal lithium-silicon alloying reaction. + The transmission channel improves ion conductivity and solves the problem of drastic volume expansion of silicon materials during charging and discharging. At the same time, ZIF-8 coated silicon spheres can be directly prepared in one step, with a simple preparation process and low cost, providing an effective way for the actual production and application of silicon-based lithium-ion battery negative electrode materials.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a metal-organic framework material-coated silicon ball lithium-ion battery negative electrode material, comprising the following steps: adding nano-silicon powder to methanol and stirring, then adding a metal-organic framework material precursor, stirring for a period of time, centrifuging, washing, and drying to obtain the metal-organic framework material-coated silicon ball lithium-ion battery negative electrode material.
[0008] Furthermore, the metal organic framework material precursors are zinc nitrate hexahydrate and dimethylimidazole.
[0009] Furthermore, the molar ratio of nano silicon powder, zinc nitrate hexahydrate and dimethylimidazole is 5-45:1:8.
[0010] Furthermore, the usage ratio of nano silicon powder and methanol is 0.02-0.06 mol:40 mL.
[0011] Furthermore, after the nano silicon powder is added into methanol, a magnetic stirrer is used for stirring.
[0012] Further, after adding zinc nitrate hexahydrate and dimethylimidazole, stirring is continued for 12-48 hours.
[0013] Furthermore, the centrifugal washing process is as follows: placing in a 50 mL centrifuge tube and centrifuging at 8000 rpm for 2 times with deionized water and 1 time with ethanol, and the centrifugation time is 5 min.
[0014] Further, the bottom precipitate was dried in a vacuum drying oven at 80°C for 12 h.
[0015] The second aspect of the present invention provides a metal organic framework material coated silicon sphere lithium ion battery negative electrode material prepared by the above preparation method.
[0016] The third aspect of the present invention provides the application of the above-mentioned ZIF-8 coated silicon sphere lithium ion battery negative electrode material in the field of lithium ion batteries.
[0017] Further, the ZIF-8 coated silicon ball lithium ion battery negative electrode material and the Super-P conductive agent, the sodium alginate binder, and the deionized water are mixed and stirred to obtain a slurry, and then the slurry is coated on the copper foil current collector. Preferably, the mass ratio of the ZIF-8 coated silicon ball lithium ion battery negative electrode material and the Super-P conductive agent and the sodium alginate binder is 8:1:1.
[0018] The specific application method is as follows: the obtained ZIF-8 coated silicon sphere is used as the active material, and the Super-P conductive agent and sodium alginate binder are mixed with deionized water in a mass ratio of 8:1:1 to make a slurry and stir continuously for 12 hours. Then the uniform slurry is slowly coated on the relatively rough side of the clean copper foil current collector as the negative electrode material, and placed in a vacuum drying oven at 80°C for 12 hours to remove water under vacuum. The negative electrode material loading is 0.8-1.1 mg cm -2 . After the negative electrode sheet was cut into a circular shape with a diameter of 10 mm using a cutting machine, a CR2032 button-type half-cell was assembled from bottom to top in an argon glove box (H2O, O2<0.01ppm) in the order of negative electrode shell, gasket, negative electrode sheet, diaphragm, electrolyte, lithium sheet, gasket, shrapnel, and positive electrode shell. The lithium sheet with a diameter of 10 mm was used as the counter electrode, the Celgard 2500 membrane was used as the diaphragm, and 1.0M LiPF6in EC:DEC:DMC=1:1:1vol%with 5.0% FEC was used as the electrolyte. After the battery was sealed with high voltage, it was required to be aged at room temperature for 12 hours before being placed in the battery test system for electrochemical performance testing.
[0019] The present invention adopts a one-step method to prepare a Si&ZIF-8 lithium ion battery negative electrode material with a high-performance special structure. The special structure mainly refers to the prepared electrode material having a core-shell structure with a thickness of about 2nm coated on the surface of a nano-silicon ball with a particle size of 10nm-100nm, and the material shows a morphology in which the nano-silicon ball and the rhombus polyhedron ZIF-8 coexist. The structure has a large specific surface area, ionic conductivity and electrochemical stability. The ZIF-8 coating layer on the surface of the nano-silicon ball can effectively buffer the huge volume expansion of silicon during lithium insertion and extraction, shortening the transmission path of lithium ions. The Si&ZIF-8 negative electrode material with a core-shell structure prepared by the present invention has a good morphology and also has excellent electrochemical performance.
[0020] The beneficial effects of the present invention are:
[0021] 1) The present invention directly prepares Si&ZIF-8 negative electrode materials through a one-step method, without high temperature or hydrothermal treatment, and the process is simple. At the same time, raw materials such as nano silicon powder, zinc nitrate hexahydrate, and dimethylimidazole are cheap and easy to obtain, which effectively reduces the production cost and provides a way for large-scale industrial production.
[0022] 2) Coating a layer of ZIF-8 on the surface of nano-silicon spheres can significantly increase their specific surface area (222.28 m 2 g -1 , pure nano silicon ball is only 32.02m 2 g -1 ), ionic conductivity, preventing the agglomeration of internal Si particles, and the rich pores of ZIF-8 itself can serve as diffusion channels to accelerate Li + It should be noted that the molar ratio of ZIF-8 and nano-silicon spheres affects the morphology of the composite material, and thus affects its electrochemical performance as a negative electrode material for lithium-ion batteries.
[0023] 3) The ZIF-8 buffer layer in the core-shell structure and the scattered ZIF-8 rhombic dodecahedrons can effectively buffer the dramatic volume expansion of the nano-silicon spheres during charging and discharging, preventing the active materials from falling off the current collector, thereby maintaining the integrity of the electrode structure and enhancing the safety performance and cycle life of the battery.
[0024] 4) Compared with pure silicon, the half-cell assembled from ZIF-8 coated nano-silicon spheres has a -1 After 450 cycles at a current density of 1.34 mAh g -1 The reversible specific capacity of pure Si is almost 0. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 This is the SEM image of the 30wt% Si & ZIF-8 powder sample in Example 1 at scales of 1 μm and 100 nm.
[0027] Figure 2 This is the TEM image of the 30wt% Si&ZIF-8 powder sample in Example 1 at a scale of 10nm.
[0028] Figure 3These are SEM images of 13wt% Si&ZIF-8, 23wt% Si&ZIF-8, 47wt% Si&ZIF-8, and 57wt% Si&ZIF-8 powder samples in Examples 2, 3, 4, and 5 at a scale of 1 μm.
[0029] Figure 4 It is the XRD diagram of 30wt% Si&ZIF-8 powder and original nano-silicon powder sample in Example 1.
[0030] Figure 5 The 30wt% Si & ZIF-8 powder in Example 1 and the original nano-silicon powder were mixed at 0.1Ag -1 Cycling performance diagram at different current densities.
[0031] Figure 6 The 30wt% Si & ZIF-8 powder in Example 1 and the original nano-silicon powder were mixed at 0.5Ag -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION
[0032] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0033] Example 1
[0034] 1.69g of nano silicon powder was added to 40mL of methanol and placed on a magnetic stirrer to start stirring. Then, 1.19g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 2.63g of dimethylimidazole (C4H6N2) were added according to the molar ratio of silicon: zinc nitrate hexahydrate: dimethylimidazole = 15:1:8. After continuous stirring for 24 hours, it was placed in a 50mL centrifuge tube and washed and centrifuged twice with deionized water at 8000rpm, and once with ethanol, and the centrifugation time was 5min. The bottom precipitate was dried in a vacuum drying oven at 80℃ for 12 hours to obtain brown ZIF-8 coated silicon sphere powder (recorded as 30wt% Si&ZIF-8).
[0035] Example 2
[0036] 0.56g of nano silicon powder was added to 40mL of methanol and placed on a magnetic stirrer to start stirring. Then, 1.19g of zinc nitrate hexahydrate and 2.63g of dimethylimidazole were added according to the molar ratio of silicon: zinc nitrate hexahydrate: dimethylimidazole = 5:1:8. After continuous stirring for 24 hours, it was placed in a 50mL centrifuge tube and washed and centrifuged twice with deionized water at 8000rpm, and once with ethanol, and the centrifugation time was 5min. The bottom precipitate was dried in a vacuum drying oven at 80℃ for 12 hours to obtain a brown ZIF-8 coated silicon sphere powder (recorded as 13wt% Si&ZIF-8).
[0037] Example 3
[0038] 1.12g of nano silicon powder was added to 40mL of methanol and placed on a magnetic stirrer to start stirring. Then, 1.19g of zinc nitrate hexahydrate and 2.63g of dimethylimidazole were added according to the molar ratio of silicon: zinc nitrate hexahydrate: dimethylimidazole = 10:1:8. After continuous stirring for 24 hours, it was placed in a 50mL centrifuge tube and washed and centrifuged twice with deionized water at 8000rpm, and once with ethanol, and the centrifugation time was 5min. The bottom precipitate was dried in a vacuum drying oven at 80℃ for 12 hours to obtain a brown ZIF-8 coated silicon sphere powder (recorded as 23wt% Si&ZIF-8).
[0039] Example 4
[0040] 1.69g of nano silicon powder was added to 40mL of methanol and placed on a magnetic stirrer to start stirring. Then, 0.60g of zinc nitrate hexahydrate and 1.31g of dimethylimidazole were added according to the molar ratio of silicon: zinc nitrate hexahydrate: dimethylimidazole = 30:1:8. After continuous stirring for 24 hours, it was placed in a 50mL centrifuge tube and washed and centrifuged twice with deionized water at 8000rpm, and once with ethanol, and the centrifugation time was 5min. The bottom precipitate was dried in a vacuum drying oven at 80℃ for 12 hours to obtain a brown ZIF-8 coated silicon sphere powder (recorded as 47wt% Si&ZIF-8).
[0041] Example 5
[0042] 1.69g of nano silicon powder was added to 40mL of methanol and placed on a magnetic stirrer to start stirring. Then, 0.40g of zinc nitrate hexahydrate and 0.88g of dimethyl imidazole were added according to the molar ratio of silicon: zinc nitrate hexahydrate: dimethyl imidazole = 45:1:8. After continuous stirring for 24 hours, it was placed in a 50mL centrifuge tube and washed and centrifuged twice with deionized water at 8000rpm, and once with ethanol, and the centrifugation time was 5min. The bottom precipitate was dried in a vacuum drying oven at 80℃ for 12h to obtain a brown ZIF-8 coated silicon sphere powder (recorded as 57wt% Si&ZIF-8).
[0043] Figure 1 The SEM image of 30wt% Si & ZIF-8 obtained in Example 1 of the present invention at a scale of 100nm and 1μm shows that the powder synthesized by this method is a composite material of nano-spherical Si and rhombic polyhedron-shaped ZIF-8. The diameter of the nano-silicon sphere is 10nm-100nm, and the side length of the rhombic polyhedron is about 300nm. Figure 2 This is a TEM image of 30wt% Si&ZIF-8 at a scale of 10nm. It can be seen that the surface of the silicon sphere is coated with a layer of ZIF-8, and the thickness of the coating layer is about 2nm. Figure 3 These are the SEM images of 13wt% Si&ZIF-8, 23wt% Si&ZIF-8, 47wt% Si&ZIF-8, and 57wt% Si&ZIF-8 powder samples in Examples 2, 3, 4, and 5 of the present invention. It can be seen that as the mass fraction of the added nanosilicon balls increases, the proportion of the rhombic polyhedron-shaped ZIF-8 in the composite material also decreases accordingly. Figure 4 Figure 3 is the XRD spectrum of 30wt% Si&ZIF-8 and original nano-silicon powder. Compared with pure silicon powder, 30wt% Si&ZIF-8 shows the characteristic peaks of Si, with crystal planes such as (111), (220), and (311) as the main characteristic peaks, and the characteristic peaks of ZIF-8 appear between 3°-20°, indicating that the product obtained in Example 1 of the present invention is a composite material of Si and ZIF-8 and does not contain other impurities.
[0044] Example 6
[0045] The ZIF-8 coated nano silicon powder was used as the active material, and the Super-P conductive agent and sodium alginate binder were mixed into a slurry at a mass ratio of 8:1:1 and stirred for 12 hours. The slurry was coated on the relatively rough side of the clean copper foil current collector as the negative electrode material using a film applicator, and placed in a vacuum drying oven at 80°C for 12 hours. After the negative electrode sheet was cut into a circular shape with a diameter of 10 mm using a cutting machine, a CR2032 button half-cell was assembled from bottom to top in an argon glove box (H2O, O2<0.01ppm) in the order of negative electrode shell, gasket, negative electrode sheet, diaphragm, electrolyte, lithium sheet, gasket, shrapnel, and positive electrode shell, wherein a lithium sheet with a diameter of 10 mm was used as the counter electrode, a Celgard 2500 membrane was used as the diaphragm, and 1.0M LiPF6 in EC:DEC:DMC=1:1:1vol%with 5.0% FEC was used as the electrolyte. After the battery is sealed with high voltage, it can be subjected to electrochemical performance testing after being aged at room temperature for 12 hours.
[0046] Comparative Example 1
[0047] Pure nano-silicon is assembled into button cells according to the method of Example 6.
[0048] Figure 5 and Figure 6 At 0.1Ag -1 and 0.5Ag -1 Cyclic performance diagram at current density of 30wt% Si & ZIF-8 in Example 1 of the present invention at 0.1Ag -1 The first cycle coulombic efficiency at the current density is 85.60%, and the discharge capacity after 55 cycles is 1826.89 mAh g -1 The coulombic efficiency is 98.94%, while the first cycle coulombic efficiency of pure nano-silicon powder is only 75.06%. The discharge capacity after 55 cycles is 577.47 mAh g -1 , the Coulombic efficiency is 98.41%. -1 When charged and discharged at a high current density of 1.34 W, although the initial discharge capacities of the two are similar, the discharge capacity of 30 wt% Si&ZIF-8 after 450 cycles is 1155.14 mAh g -1 , while the discharge capacity of pure nano-silicon powder dropped sharply to 13.89 mAh g -1 , the cycle stability is poor.
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal organic framework material coated silicon sphere lithium ion battery negative electrode material, characterized in that: The metal organic framework material coated silicon sphere lithium ion battery negative electrode material shows a mixed morphology of rhombic dodecahedron-shaped ZIF-8 and spherical nano-silicon, and the surface of the silicon sphere is also coated with a layer of ZIF-8; The particle size of the nano-silicon spheres is 10nm to 100nm; the thickness of the ZIF-8 layer on the surface of the silicon spheres is 2nm; The preparation method comprises the following steps: adding nano silicon powder into methanol and stirring, then adding metal organic framework material precursor, stirring for a period of time, centrifugally washing and drying to obtain the metal organic framework material coated silicon ball lithium ion battery negative electrode material; The metal organic framework material precursor is zinc nitrate hexahydrate and 2-methylimidazole; The molar ratio of nano silicon powder, zinc nitrate hexahydrate and 2-methylimidazole is 5-45:1:8; The centrifugal washing process is: placing in a 50 mL centrifuge tube and centrifuging at 8000 rpm for 2 times with deionized water and 1 time with ethanol, and the centrifugation time is 5 minutes.
2. The preparation method according to claim 1, characterized in that: The usage ratio of nano silicon powder and methanol is 0.02-0.06 mol:40 mL.
3. The preparation method according to claim 1, characterized in that: After adding the nano silicon powder into methanol, a magnetic stirrer is used for stirring.
4. The preparation method according to claim 1, characterized in that: After adding zinc nitrate hexahydrate and 2-methylimidazole, stirring is continued for 12-48 hours.
5. The preparation method according to claim 1, characterized in that: The bottom precipitate was dried in a vacuum oven at 80°C for 12 h.
6. A metal organic framework material coated silicon sphere lithium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 5.
7. Application of the metal organic framework material coated silicon sphere lithium ion battery negative electrode material according to claim 6 in the field of lithium ion batteries.
8. The use according to claim 7, characterized in that: The metal organic framework material-coated silicon ball lithium ion battery negative electrode material and Super-P conductive agent, sodium alginate binder and deionized water are mixed and stirred to obtain a slurry, and then the slurry is coated on a copper foil current collector.
9. The use according to claim 8, characterized in that: The mass ratio of metal organic framework material coated silicon sphere lithium ion battery negative electrode material and Super-P conductive agent and sodium alginate binder is 8:1:1.
Citation Information
Patent Citations
ZIF-8 / silicon composite nano-column array electrode and preparation method thereof
CN105680001A